Voice Without Choice? Investigating Adolescent Girls' Agency in Marital Decision-making in Niger. (October 2020) - Saul, Grace; Diarra, Aïssa; Melnikas, Andrea J.; Amin, Sajeda
This article uses qualitative data from Niger to examine adolescent girls' perceptions of their own agency in marriage decisions and contextual factors influencing these perceptions. We find that girls make marital decisions within a context that stresses parental consent and community approval, places a high value on obedience, and is constrained by limited opportunities, gendered distribution of labor, and dominant social norms promoting an early and narrow 'window of opportunity' for marriage. Findings demonstrate that interventions aiming to delay marriage in Niger must work to influence both community norms supporting child marriage and girls' own motivations in martial decision-making.